Mean Platelet Volume: Is It a Predictive Parameter in Diagnosis of Acute Mesenteric Ischemia? - Türkoğlu, Ahmet (Int Surg, 2015)
Our objective for this study was to discuss the usability of mean platelet volume, which is associated with numerous vascular pathologies, in the early diagnosis of acute mesenteric ischemia. Acute mesenteric ischemia is an uncommon, life-threatening clinical condition mostly seen in the elderly. Early diagnosis of acute mesenteric ischemia and correction of blood circulation before necrosis occurs are important factors affecting prognosis. A total of 95 patients who underwent emergency surgery for acute mesenteric ischemia and 90 healthy volunteers as control group were included in this study. Age, gender, hemoglobin values, white blood cell counts, mean platelet volume, and platelet counts are recorded for evaluation. The mean platelet volume values were significantly higher in patients with acute mesenteric ischemia than in the controls (9.4 ± 1.1 fL and 7.4 ± 1.4 fL, respectively; P < 0.001). Receiver-operating characteristic analysis demonstrated a cutoff value of mean platelet volume as 8.1 fL (area under the curve, 0.862), a sensitivity of 83.2%, and a specificity of 80%. As a result, in the patients who are admitted to the hospital with acute nonspecific abdominal pain and suspected of having acute mesenteric ischemia, high mean platelet volume values in routine hemograms support the diagnosis of acute mesenteric ischemia.